Heuristic inspired search method for fast wedgelet pattern decision in 3D-HEVC - Jaballah, Sami; Larabi, Mohamed-Chaker; Tahar, Jamel Belhadj (2016 6th European Workshop on Visual Information Processing (EUVIP), 2016)
The 3D High Efficiency Video Coding (3D-HEVC) is the latest 3D extension of the HEVC video coding standard. It supports multi-view videos plus depth (MVD), which is a sophisticated format for enhanced 3D content. Depth modeling modes (DMM) are adopted in the 3D-HEVC for better sharp edge encoding. However, employing DMM causes important computational complexity. In this paper, we propose a new method for fast wedgelet pattern decision in 3D-HEVC. In order to avoid unnecessary evaluation of the DMMs, a new early termination based on the smoothness of the current block is adopted. Besides, based on the shuffled frog leaping algorithm, a new heuristic method to search the optimal wedgelet pattern for DMM1 Depth mode is introduced. The proposed algorithm outperforms the HTM16.0 implemented scheme in terms of encoding time with similar coding efficiency.